HLA Antibody Detection With Solid Phase Assays: Great Expectations or Expectations Too Great?. Issue 9 (1st August 2014) - Gebel, H. M.; Bray, R. A.
<x xml:space="preserve">Abstract</x> Alloantibodies directed against HLA antigens, are a barrier to long‐term solid organ allograft survival. The clinical impact of preformed, donor‐directed HLA alloantibodies range from acceptable risk to unequivocal contraindication for organ transplantation. HLA antibodies are key factors that limit patient access to donor organs. Serological methods were once the only approach to identify HLA antigens and antibodies. Limitations in these technologies led to the development of solid phase approaches. In the early 1990s, the development of the polymerase chain reaction enabled DNA‐based HLA antigen testing to be performed. By the mid‐1990s, microparticle‐based technology that utilized flow cytometry for analysis was developed to detect both classes I and II HLA antibodies. These methodologies revolutionized clinical histocompatibility testing. The strengths and weaknesses of these assays are described in detail in this review.